The nonlinear relationship between monetary policy and financial deepening in an oil-exporting economy: Evidence from Saudi Arabia - Ryoji, Sato; Gamal, Awadh Ahmed Mohammed; Tha, Gan Pei; David, Joseph; Rambeli, Norimah (Asian Journal of Economic Modelling, 2025)
This study explores the asymmetric impact of monetary policy on financial deepening in Saudi Arabia from 1992 to 2022. It uses the nonlinear autoregressive distributed lag (NARDL) bounds-testing method to show that there is strong evidence of a long-term link between financial deepening and the sums of monetary policy and control variables. The findings indicate that financial deepening responds nonlinearly to monetary policy shocks. Specifically, both positive and negative shifts in monetary policy encourage financial deepening, but positive shifts have a more significant effect. Additionally, monetary uncertainty and economic activity levels notably influence financial deepening. The study suggests that policymakers should use tools like changing interest rates and managing inflation to help the economy become more diverse, deepen the financial system, and lower short-term monetary risks. This will ensure that the financial sector continues to grow.